Indexed bonds and revisions of inflation expectations - Andreas Reschreiter (Institute for Advanced Studies (IHS), 2006)
This paper investigates the impact of revisions in inflation expectations on the prices of UK inflation-indexed and conventional government bonds with a vector autoregressive (VAR) model. Downwards revisions of inflation expectations are associated with unexpected increases in the prices of conventional bonds, but the prices of indexed bonds are not significantly affected. This suggests that indexed bonds protect investors against inflation while nominal bonds are exposed to changing monetary conditions. This is consistent with the view that indexed bonds avoid the inflation risk premium of conventional bonds and reduce the government's long-run borrowing costs.
Keywords: E43; G12; 330; conventional and indexed bonds; inflation; macroeconomy; VAR; Öffentliche Anleihe; Inflationserwartung; VAR-Modell; Großbritannien